2022
DOI: 10.3324/haematol.2022.280637
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose tyrosine kinase inhibitors in patients with chronic myeloid leukemia: a retrospective study in China

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
(18 reference statements)
1
10
1
1
Order By: Relevance
“…Moreover, dose-halving therapy yields higher molecular recurrence-free survival rate compared to direct TKI discontinuation ( Luo et al, 2022 ). Our recent study also confirmed the feasibility of TKI dose reduction therapy for Chinese CML patients ( Chen et al, 2022 ). The concern of whether dose reduction before TKI discontinuation affects patient’s access to TFR is also of interest to investigators.…”
Section: Introductionsupporting
confidence: 76%
“…Moreover, dose-halving therapy yields higher molecular recurrence-free survival rate compared to direct TKI discontinuation ( Luo et al, 2022 ). Our recent study also confirmed the feasibility of TKI dose reduction therapy for Chinese CML patients ( Chen et al, 2022 ). The concern of whether dose reduction before TKI discontinuation affects patient’s access to TFR is also of interest to investigators.…”
Section: Introductionsupporting
confidence: 76%
“…These limited prospective results demonstrated that low‐dose TKI is feasible and effective in newly diagnosed patients or patients with MMR. In our previous study, seven out of ten patients not in MMR achieved MMR or deeper molecular response with low‐dose treatment 36 . In a study of patients with prior TKI intolerance treated with low‐dose ponatinib, 40.4% patients had improved treatment response over a median of 19.2 months of ponatinib treatment 37 .…”
Section: Discussionmentioning
confidence: 92%
“…In our previous study, seven out of ten patients not in MMR achieved MMR or deeper molecular response with low‐dose treatment. 36 In a study of patients with prior TKI intolerance treated with low‐dose ponatinib, 40.4% patients had improved treatment response over a median of 19.2 months of ponatinib treatment. 37 These limited results suggested that low‐dose TKI could improve treatment response, but prospective studies with large samples are still needed to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Первоначально дозы ИТК разрабатывались в рамках стратегии, аналогично используемой для химиотерапии, т. е. дозы, на один уровень ниже максимально переносимой. Позднее было установлено, что эффективность препарата может быть аналогичной или сохраняться после достижения ответа при более низких дозах ИТК [70,77,[82][83][84]. Продолжительный опыт применения ИТК при ХМЛ обозначил новую концепцию в терапии опухоли -разработку долгосрочной таргетной терапии в оптимальной биологической дозе [85][86][87][88].…”
Section: сниженные дозы ингибиторов тирозинкиназ: кому и когдаunclassified